Expression of hemerythrin-like genes from the obligate aerobe Myxococcus xanthus improves the growth of the industrially relevant Gluconobacter oxydans - Fleegal, Alexa L.; Stenzel, Mason J.; Schweiger, Paul; Bretl, Daniel J. (Frontiers in Microbiology, 2025)
Myxococcus xanthus is a ubiquitous, obligately aerobic soil bacterium. M. xanthus has many two-component systems that serve to regulate responses to environmental stimuli. One of these systems, the multicomponent signaling system named the NmpRSTU pathway has been demonstrated to regulate genes that are predicted to be important for oxygen utilization, including the gene mxan_5531, which encodes a predicted hemerythrin-like protein. The family of proteins that includes hemerythrin-like proteins binds oxygen coordinated by a di-iron cofactor. Based on the sequence alignments and predictive structural analysis, we have determined that M. xanthus encodes at least five other predicted hemerythrin-like proteins. Of these six proteins predicted to be hemerythrin-like proteins, four were biochemically confirmed to bind oxygen in vitro using UV-spectroscopy. Currently, little is known about M. xanthus oxygen-dependent phenotypes, and the role of these hemerythrin-like proteins in M. xanthus is undescribed. To assess possible in vivo function, we chose to examine the impact of heterologous expression in the industrially relevant bacterium Gluconobacter oxydans. This bacterial species is used industrially to oxidize sugars to produce vinegar, vitamin C, the anti-diabetic drug miglitol, and several other products. However, due to its high oxygen demand, G. oxydans has a relatively slow growth rate under industrial-scale conditions. The expression of five of the hemerythrin-like proteins in G. oxydans led to faster doubling times and increased cell densities.